Lignification of Sheepgrass Internodes at Different Developmental Stages and Associated Alteration of Cell Wall Saccharification Efficiency - Wang, Jianli; Ma, Lichao; Shen, Zhongbao; Sun, Dequan; Zhong, Peng; Bai, Zetao; Zhang, Hailing; Cao, Yingping; Bao, Yan; Fu, Chunxiang (Frontiers in Plant Science, 2017)
Sheepgrass (Leymus chinensis) is a high-quality cool-season forage crop used as pasture and hay for livestock feeds. The presence of lignin in cell walls, however, impairs forage digestibility of such lignocellulosic feedstock. Here, the structural characterization and cell wall composition of sheepgrass internodes were studied, and a progressive increase in cell wall lignification was observed with internode maturation. Lignin composition analysis further revealed a gradual accumulation of guaiacyl and syringyl lignin units during internode development. Consistently, the transcript abundance of lignin-related genes was upregulated in mature internodes, suggesting their potential roles in lignin biosynthesis. Furthermore, the effects of cell wall composition and lignification extent on biomass saccharification efficiency were examined in sheepgrass. The results showed that lignin content, guaiacyl and syringyl lignin unit levels inversely correlated with cell wall digestibility, indicating that lignin is a crucial obstacle for utilizing sheepgrass feedstock. The baseline information obtained in this work will facilitate establishment, grazing management, harvesting and feedstock utilization of sheepgrass in future.